Sustaining paradise: How tourism-driven growth affects environmental sustainability and community welfare in Bali - Purba, Ida Bagus Agung Haridharma; Yuliarmi, Ni Nyoman; Suasih, Ni Nyoman Reni; Setyari, Ni Putu Wiwin (Edelweiss Applied Science and Technology, 2025)
Tourism-driven growth has become the backbone of regional development in Bali. However, the rapid expansion of this sector has triggered critical trade-offs between economic gains and ecological resilience. This study examines the direct effect of tourism-driven growth on community welfare and its indirect effect through environmental sustainability in nine districts of Bali from 2014 to 2023. Panel data are analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Tourism-driven growth is measured by its contribution to gross regional domestic product, share of tourism employment, and share of tourism investment. Environmental sustainability is measured by clean water availability, food crop productivity, and energy efficiency. Community welfare is measured by poverty rate, income equality, and human development index. Results show that tourism-driven growth increases community welfare but reduces environmental sustainability through greater resource use and ecological pressure. Environmental sustainability improves community welfare and partially mediates the relationship between tourism-driven growth and community welfare, reducing welfare gains when environmental quality declines. The negative impact is strongest in high-intensity tourism areas with fragile ecosystems. Long-term welfare gains require integrating tourism planning with environmental safeguards, enforcing zoning, improving water and energy efficiency, and promoting eco-tourism in less-developed districts to reduce disparities and protect resources.